The Effect of Good Corporate Governance on Leverage-Mediated Dividend Policy in LQ45 Companies Listed on IDX - Yoshi Suryo Dhanti; Totok Sugiharto (Cakrawala Repositori IMWI, 2024)
The objectives of this study are to investigate the relationship between Good Corporate Governance (GCG) variables, leverage, and dividend policy, as well as to examine the effect of leverage-mediated GCG on dividend policy. This study was conducted on companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) spanning from 2018-2022. Data were gathered from the companies’ annual financial statements using purposive sampling methods and judgment sampling. The collected data were analyzed using Partial Least Square analysis – SEM, SMART PLS software to determine the relationship between variables. The findings reveal a positive influence between GCG and dividend policy, with leverage mediating this relationship. These results diverge from certain previous studies, so the results of this test can provide a variation of research results. The implications of this study are expected to enhance understanding regarding the important role of GCG and its relation to dividend policy.